2016
DOI: 10.1093/chromsci/bmw161
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Imprinted Solid Phase Extraction using Bismethacryloyl-β-cyclodextrin and Methacrylic Acid as Double Functional Monomers for Selective Analysis of Glycyrrhizic Acid in Aqueous Media

Abstract: In this work, a new molecularly imprinted solid phase extraction protocol was developed for the selective extraction and purification of glycyrrhizic acid from liquorice roots in aqueous media. The molecularly imprinted polymers (MIPs) for glycyrrhizic acid were prepared by using bismethacryloyl-β-cyclodextrin and methacrylic acid as double functional monomers and characterized by Fourier transform infrared spectroscopy, scanning electron microscope, thermo gravimetric analysis, nitrogen adsorption and element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Tang et al. [ 26 ] used bismethacryloyl‐β‐cyclodextrin and MAA as double functional monomers to prepare MIP. The MIP exhibited high selectivity for glycyrrhizic acid in the presence of its structural analogs hesperidin and methyl hesperidin.…”
Section: Molecularly Imprinted Polymers With Cyclodextrin As Functional Monomersmentioning
confidence: 99%
“…Tang et al. [ 26 ] used bismethacryloyl‐β‐cyclodextrin and MAA as double functional monomers to prepare MIP. The MIP exhibited high selectivity for glycyrrhizic acid in the presence of its structural analogs hesperidin and methyl hesperidin.…”
Section: Molecularly Imprinted Polymers With Cyclodextrin As Functional Monomersmentioning
confidence: 99%
“…The novel advances in MIT have resulted in the appearance of synthetically engineered MIPs incorporated with cyclodextrins (CDs) in an imprinted polymeric framework with the improved performance [ 123 , 124 , 125 ]. CDs are cyclic oligosaccharide structures established by d -glucopyranose units consist of 6 (α-CD), 7 (β-CD) and 8 (γ-CD) d -Glucose Monomer, that are linked by glycosidic bonds [ 126 ].…”
Section: Magnetic Molecularly Imprinted Polymer (Mmip) Preparationmentioning
confidence: 99%
“…To date, the advances in MIT have led to the development of novel synthetically engineered MIPs material that is incorporated with α/β/γ-CDs within an imprinted polymeric framework, which fortunately improved the performance of MIPs [ 123 , 124 , 125 ] due to their hydrophilic outside and hydrophobic inner space and formation of a non-covalent complex with the guest molecule. Hydrophobic drugs can enter the lipophilic CD cavity with their whole structure or partially.…”
Section: Prospects and Conclusionmentioning
confidence: 99%
“…Other different linkers reported in the literature are bifunctional isocyanate linkers [ 105 ] and 1,4-phenylenediisocyanate [ 106 ], both used to obtain cyclodextrin-based polymeric materials as supramolecular sorbents for environmental remediation in aqueous samples. SPE of pollutants such as diphenylphthalate, phenolic compounds, glycyrrhizic acid, and pyrethroids was achieved by using molecularly imprinted polymers of allyl-β-cyclodextrin and methacrylic acid [ 107 ], β-CD functionalized ionic liquid polymers [ 108 ], molecularly imprinted polymers with bismethacryloyl-β-cyclodextrin and methacrylic acid as double functional monomers [ 109 ], and a namely hyperbranched polymer functionalized with cyclodextrin [ 110 ]. Ibuprofen is a drug of environmental concern, since it has been found that pharmaceutical substances are commonly found in the environment and cause negative impacts on aquatic life.…”
Section: Deeping In: the Environmental Benefits Of Using Cyclodextmentioning
confidence: 99%